2020
DOI: 10.1186/s12879-020-05390-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgery combined with antibiotics for the treatment of endogenous endophthalmitis caused by liver abscess

Abstract: Backgrounds Endogenous endophthalmitis is a serious disease caused by intraocular infection that can rapidly progress to cause blindness. This study evaluated the clinical features, surgical and antibiotics treatment strategies, and treatment outcomes in patients with endophthalmitis caused by liver abscess. Methods Between April 2014 and April 2019, the clinical data of 16 patients (19 eyes) with endophthalmitis associated with liver abscess who underwent surgery at Shengjing Hospital were retrospectively a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Ocular findings included chemosis, red painful eye, haze cornea, and vitreous. Decreased visual acuity at presentation of hand movement or less and hypopyon were associated with poor prognosis [ 15 , 68 , 72 , 75 , 76 , 77 ]. Patients with unilocular involvement were found to be a risk factor for evisceration, in comparison with bilateral infection, one possible explanation being the delay in presentation in cases in which only one eye was affected [ 16 ].…”
Section: Diagnostic Of Endogenous Hvkp Endophthalmitismentioning
confidence: 99%
See 2 more Smart Citations
“…Ocular findings included chemosis, red painful eye, haze cornea, and vitreous. Decreased visual acuity at presentation of hand movement or less and hypopyon were associated with poor prognosis [ 15 , 68 , 72 , 75 , 76 , 77 ]. Patients with unilocular involvement were found to be a risk factor for evisceration, in comparison with bilateral infection, one possible explanation being the delay in presentation in cases in which only one eye was affected [ 16 ].…”
Section: Diagnostic Of Endogenous Hvkp Endophthalmitismentioning
confidence: 99%
“…ESBL strains were identified in up to 10–13% of cases [ 40 , 57 , 58 , 61 ]. In a recent study on 110 patients with KPLA, with a mean follow-up period of 3.65 years, Wang et al [ 76 ] found that ESBL was encountered significantly more frequently in the patients who experienced recurrence (30.0% vs. 8.89%). This finding supports the idea that ESBL should be considered an independent risk factor for the recurrence of KPLA [ 76 ].…”
Section: Management Of Ekementioning
confidence: 99%
See 1 more Smart Citation
“…The organisms most frequently isolated during infection are Streptococcus species, Klebsiella pneumoniae and Escherichia coli. Occasionally, cases of other etiology are also reported [ 22 , 23 ].…”
Section: Primary Source Of Infectionmentioning
confidence: 99%
“…The prognosis of EE in the course of liver abscess is poor. Many reported cases end in enucleation or a lack of sense of light [ 4 , 23 ]. A good visual outcome is possible only in the case of a very rapid implementation of intensive treatment.…”
Section: Primary Source Of Infectionmentioning
confidence: 99%